Thermal annealing effect on the band gap and dielectric functions of silicon nanocrystals embedded in SiO2 matrix - Ding, Liang (2010)
The thermal annealing effect on band gap and dielectric functions of silicon nanocrystals (nc-Si) embedded in a SiO2 matrix synthesized by Si ion implantation is investigated by spectroscopic ellipsometry. A large band-gap expansion of nc-Si relative to bulk crystalline silicon has been observed. The band gap of the nc-Si for the nonannealing condition (i.e., as implanted) is 1.78 eV while it is 1.72 eV for the annealing at 1000 °C for 100 min. The slight decrease in the band gap is attributed to the slight increase in the nc-Si size with annealing. The dielectric functions of nc-Si show a significant suppression, as compared to bulk crystalline silicon, due to the quantum size effect. Annealing results in a small change in the static dielectric constant, which can be explained in terms of the size effect also.